Answers

2014-10-14T18:53:16+05:30

This Is a Certified Answer

×
Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.
Try to factorise the polynomial to get the factor (x+1).

4x³ + 7x² - 3x - 6
= 4x³ + 4x² + 3x² + 3x - 6x - 6
= 4x²(x+1) + 3x(x+1) - 6(x+1)

Now take (x+1) common
(x+1)(4x²+3x-6)

So 4x³ + 7x² - 3x - 6 = (x+1)(4x²+3x-6)

By dividing 4x³ + 7x² - 3x - 6 by (x+1),

 \frac{4 x^{3}  + 7 x^{2} - 3x - 6}{x+1}

=
 \frac{(x+1)(4 x^{2} +3x-6)}{x+1}

=
4 x^{2} +3x-6 
1 5 1
please do this question in detail so edit your answer.
4x³ + 7x² - 3x - 6
= 4x³ + 4x² + 3x² + 3x - 6x - 6
= 4x²(x+1) + 3x(x+1) - 6(x+1)

Now take (x+1) common
(x+1)(4x²+3x-6)

So 4x³ + 7x² - 3x - 6 = (x+1)(4x²+3x-6)

By dividing 4x³ + 7x² - 3x - 6 by (x+1), we get 4x²+3x-6.
thanks